Ollier disease and Maffucci syndrome are caused by somatic mosaic mutations of IDH1 and IDH2 - Amary, M Fernanda; Damato, Stephen; Halai, Dina; Eskandarpour, Malihe; Berisha, Fitim; Bonar, Fiona; McCarthy, Stan; Fantin, Valeria R; Straley, Kimberly S; Lobo, Samira; Aston, Will; Green, Claire L; et al. (Nature genetics, 2011)
Adrienne Flanagan and colleagues report the identification of somatic mosaic mutations in the IDH1 and IDH2 genes in tumors from individuals with Ollier disease and Maffucci syndrome, diseases that are characterized by the presence of multiple central cartilaginous tumors that are accompanied by soft tissue hemangiomas in Maffucci syndrome. Ollier disease and Maffucci syndrome are characterized by multiple central cartilaginous tumors that are accompanied by soft tissue hemangiomas in Maffucci syndrome. We show that in 37 of 40 individuals with these syndromes, at least one tumor has a mutation in isocitrate dehydrogenase 1 ( IDH1 ) or in IDH2 , 65% of which result in a R132C substitution in the protein. In 18 of 19 individuals with more than one tumor analyzed, all tumors from a given individual shared the same IDH1 mutation affecting Arg132. In 2 of 12 subjects, a low level of mutated DNA was identified in non-neoplastic tissue. The levels of the metabolite 2HG were measured in a series of central cartilaginous and vascular tumors, including samples from syndromic and nonsyndromic subjects, and these levels correlated strongly with the presence of IDH1 mutations. The findings are compatible with a model in which IDH1 or IDH2 mutations represent early post-zygotic occurrences in individuals with these syndromes.